Limosilactobacillus reuteri HM108 alleviates obesity in rats fed a high-fat diet by modulating the gut microbiota, metabolites, and inhibiting the JAK-STAT signalling pathway - Tang, Mi; Li, Xianping; Ren, Jiahui; Yao, Chunyu; Liu, Lu; Li, Xiaojing; Yuan, Xueping; Zhao, Junying; Liu, Bin; Qiao, Weicang; Chen, Lijun (Frontiers in Nutrition, 2025)
IntroductionObesity is a globally prevalent metabolic disease, and high-calorie diets are major contributors to its development. Probiotic interventions can modulate the gut flora and alleviate systemic and low-grade inflammation, making them potential in-terventions for alleviating metabolic syndrome.MethodsThis study explored the beneficial effects of the Limosilactobacillus reuteri HM108 strain derived from breast milk on obesity in high-fat diet-induced rats using a multi-gradient concentration in-tervention. Serum biochemical markers and inflammatory mediators were determined using enzyme-linked immunosorbent assay after 6-week intervention. Gut microbiota was assessed using 16S rRNA sequencing. The levels of short-chain fatty acid were detected using gas chromatography–mass spectrometry, fecal metabolites were ana-lysed using untargeted metabolomics, and the liver tissue was subjected to tran-scriptomics analysis.Results and discussionThe findings indicated that L. reuteri HM108 mitigated obesity, reduced blood lipids levels and immune factors, as well as altered the gut mi-crobiota composition, including reducing the Firmicutes/Bacteroidetes ratio. L. reuteri HM108 also inhibited the JAK-STAT signalling pathway. L. reuteri HM108 alleviates obesity caused by a high-fat diet in rats, offering a theoretical foun-dation and practical insights for utilizing this strain in obesity management.